2014
DOI: 10.1007/s00423-014-1267-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute acalculous cholecystitis in the critically ill: risk factors and surgical strategies

Abstract: We suggest a three-pronged approach to surgical resolution of AAC. Patients that are healthy enough to tolerate LC should undergo LC early in the course of the disease. In critically ill patients, patients with multiple comorbidities, a high conversion risk, or who are poor surgical candidates, PC may be the safest and most successful intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 69 publications
0
41
0
2
Order By: Relevance
“…48 Treinen et al have also suggested that PC may be the safest and most successful intervention in patients unfit for surgery. 49 Thus, we hypothesize that adequate bile drainage plays an important role in reducing recurrent AC.…”
Section: Discussionmentioning
confidence: 99%
“…48 Treinen et al have also suggested that PC may be the safest and most successful intervention in patients unfit for surgery. 49 Thus, we hypothesize that adequate bile drainage plays an important role in reducing recurrent AC.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these patients experienced mortality during the index admission. Emergency LC was performed in 3 patients with AAC early during the index admission because they were fit enough for the procedure, in keeping with published guidance [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PC prevents further complications in up to 85% of patients [2,14]. Indeed, in the critically ill, PC has been shown to have lower morbidity, mortality and shorter length-of-hospital stay compared to cholecystectomy [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Unterschied zur kalkulösen Cholezystitis haben 25 % der Patienten mit einer akalkulösen Cholezystitis als erstes klinisches Zeichen ein unerklärliches Fieber. Im Verlauf kommen klassische Symptome wie rechtsseitige Oberbauchschmerzen mit einem positiven Murphy-Zeichen sowie Übelkeit und Erbrechen hinzu [58]. Die Evaluation der genannten klinischen Zeichen ist bei einem intensivmedizinisch betreuten Patienten z.…”
Section: Diagnostikunclassified